2008
DOI: 10.1109/tpwrs.2008.920731
|View full text |Cite
|
Sign up to set email alerts
|

When Supply Meets Demand: The Case of Hourly Spot Electricity Prices

Abstract: We use a supply-demand framework to model the hourly day-ahead spot price of electricity based on publicly available information. With the model we can forecast the level and the probability of a spike in the spot price defined as the spot price being above a certain threshold. Several European countries have recently started publishing day-ahead forecasts of the available supply. In this paper we show potential uses of such indicators and test their forecasting power in an hourly spot price model. We conclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…It is commonly assumed that the spot price S t is a function of the demand D t and the installed capacity C t in terms of the demand-supply ratio (DSR) r SD,t =1−D t /C t , i.e., S t =f(r SD,t ). Boogert and Dupont (2008) studied the Dutch electricity market structure and showed that, as expected, the spot price is a decreasing function of DSR. A drawback for using this approach is that estimates of available capacity are not published for the Canadian markets.…”
Section: Resultssupporting
confidence: 53%
“…It is commonly assumed that the spot price S t is a function of the demand D t and the installed capacity C t in terms of the demand-supply ratio (DSR) r SD,t =1−D t /C t , i.e., S t =f(r SD,t ). Boogert and Dupont (2008) studied the Dutch electricity market structure and showed that, as expected, the spot price is a decreasing function of DSR. A drawback for using this approach is that estimates of available capacity are not published for the Canadian markets.…”
Section: Resultssupporting
confidence: 53%
“…Some authors have given special attention to such effects by directly modeling the behaviour of the 'reserve margin' C t − D t (or the percentage reserve margin 1 − D t /C t ), emphasizing the advantage of capturing both demand and capacity movements in a single variable. Boogert and Dupont [16] analyse the relationship between margin and spot price as well as margin and spike probability, and suggest a nonparametric approach. Cartea et al [35] advocate using forward-looking margin information as an indicator of when a spike is likely to occur, and defining a separate price regime when a threshold level of margin is reached.…”
Section: Price Relationship With Capacity or Marginmentioning
confidence: 99%
“…• Fixed price thresholds where all prices exceeding some subjectively chosen price level (e.g., 100 EUR/MWh) are classified as spikes (Boogert and Dupont, 2008;Lapuerta and Moselle, 2001). Graphical techniques, like the sample mean excess function, might be used for the selection of a more optimal cutoff level (Fanone et al, 2012); however, this procedure can hardly be automated.…”
Section: Identification Of Spikesmentioning
confidence: 99%